Octaarginine-modified gold nanoparticles enhance the radiosensitivity of human colorectal cancer cell line LS180 to megavoltage radiation - Zhang XY (Dove Medical Press, 2018)
Xuyang Zhang,1 Hao Wang,1 Jonathan Andrew Coulter,2 Ruijie Yang1 1Department of Radiation Oncology, Peking University Third Hospital, Beijing, China; 2School of Pharmacy, Queen’s University of Belfast, Belfast, UK Background: This study investigated the effectiveness and underpinning mechanisms of radiosensitization using octaarginine (R8)-modified gold nanoparticle–poly(ethylene glycol) (GNP-PEG-R8) in colorectal cancer cell line LS180 to megavoltage radiotherapy in vitro. Method: In-house synthesized GNP-PEG was characterized by transmission electron microscopy, dynamic light scattering, ultraviolet–visible spectrophotometry, and X-ray photoelectron spectroscopy. Inductively coupled plasma mass spectroscopy was used to quantify internalization. Direct cytotoxicity was established using the Cell Counting Kit-8, while radiosensitivity was determined using the gold standard in vitro clonogenic assay. Cell-cycle distribution, apoptosis, reactive oxygen species (ROS), and mitochondrial membrane potential (MMP) were analyzed by flow cytometry, further exploring the key mechanisms driving GNP-PEG-R8 radiosensitization. Results: The core GNP diameter was 6.3±1.1 nm (mean±SD). Following functionalization, the hydrodynamic diameter increased to 19.7±2.8 nm and 27.8±1.8 nm for GNP-PEG and GNP-PEG-R8, with respective surface plasmon resonance peaks of 515 nm and 525 nm. Furthermore, incorporation of the R8 significantly increased nanoparticle internalization compared to GNP-PEG (p<0.001) over a 1 h treatment period. Functionalized GNPs confer little cytotoxicity below 400 nM. In clonogenic assays, radiation combined with GNP-PEG-R8 induced a significant reduction in colony formation compared with radiation alone, generating a sensitizer enhancement ratio of 1.59. Furthermore, GNP-PEG-R8 plus radiation predominantly induced cell-cycle arrest in the G2/M phase, increasing G2/M stalling by an additional 10% over GNP-PEG, markedly promoting apoptosis (p<0.001). Finally, ROS levels and alterations in MMP were investigated, indicating a highly significant (p<0.001) change in both parameters following the combined treatment of GNP-PEG-R8 and radiation over radiation alone. Conclusion: R8-modified GNPs were efficiently internalized by LS180 cells, exhibiting minimal cytotoxicity. This yielded significant radiosensitization in response to megavoltage radiation. GNP-PEG-R8 may enhance radiosensitivity by arresting cell cycle and inducing apoptosis, with elevated ROS identified as the likely initiator. Keywords: gold nanoparticles, octaarginine, colorectal cancer, megavoltage radiotherapy, mechanisms, radiosensitization